Small Firms in Cross-Border Business Networks with the CEEC: Evidence From Austria - Peter Huber (Austrian Institute of Economic Research (WIFO), 2003)
This paper analyses the co-operation activities of small Austrian firms with the CEEC and compares them to those of larger firms. Small firms are less likely to engage in cross-border co-operation than larger firms, more likely to co-operate in ownership based forms of co-operation but less likely to engage in production or sales activities. Finally, small firms are more likely to have small partners. I also find that small firms' co-operation probability depends more strongly on distance considerations and internal organisation of the firm but that small firms profit less from previous experiences with cooperation than larger firms. Differences in large firms' characteristics explain around 30% to 40% of the lower co-operation probability. The remaining 60% to 70% are due to differences in small firm behaviour. The paper concludes by drawing attention to the policy implications of these results.
Keywords: D23; L10; R12; 330; Cross Border Cooperation; Small firms; Networks; Kleinstunternehmen; Unternehmenskooperation; Unternehmensnetzwerk; Schätzung; Österreich; Osteuropa